2010
DOI: 10.3111/13696998.2010.540874
|View full text |Cite
|
Sign up to set email alerts
|

Work productivity loss due to flares in patients with chronic gout refractory to conventional therapy

Abstract: Flares in patients with chronic gout refractory to conventional therapy significantly affect patient work productivity and social activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 13 publications
3
67
0
5
Order By: Relevance
“…A possible explanation for less educated people feeling more pain is that they have less knowledge about the importance of adequate pain evaluation and management and less financial conditions, they frequently self-medicate and have less access to health services. Studies have also shown that pain affects professional productivity and social life 12 . A study carried out in Turkey with 1600 hospital employees has shown that 65.8% of them had low back pain, especially health professionals 13 , and that administrative and production area employees, after autonomous workers, were the most affected by chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for less educated people feeling more pain is that they have less knowledge about the importance of adequate pain evaluation and management and less financial conditions, they frequently self-medicate and have less access to health services. Studies have also shown that pain affects professional productivity and social life 12 . A study carried out in Turkey with 1600 hospital employees has shown that 65.8% of them had low back pain, especially health professionals 13 , and that administrative and production area employees, after autonomous workers, were the most affected by chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Gout significantly reduces quality of life (5) and increases the use of health care facilities (6)(7)(8) and absenteeism from work (8). Gout is also an important independent risk factor of cardiovascular morbidity and mortality (9).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, глобальное распространение ожирения также способствует «эпидемии» гиперурикемии [6,7,9] Следует отметить, что подагра связана со значитель-ными экономическими затратами [13,14]. Так, длитель-ность временной нетрудоспособности у пациентов с подагрой моложе 65 лет составляет 25,1 дня в год, а эпизоды острой подагры приводят к потере в среднем 17,1 дня трудоспособности в год [15]. Febuxostat, a selective inhibitor of isoforms xantinoxydoreductase, it is an alternative to a limited number of medications to reduce urates levels applied in recent decades.…”
unclassified